Four new species and a new record of Anchocerus from the Oriental region (Coleoptera: Staphylinidae: Staphylininae: Staphylinini: Acylophorina) - Janák, Jiří (Zootaxa, 2017)
Four new species of the genus Anchocerus Fauvel, 1905 were described and illustrated: A. balianus sp. nov. from Bali, A. differens sp. nov. and A. rougemonti sp. nov., both from Sabah (Borneo), and A. thai sp. nov. from Thailand. Additional records of A. aparamerus Solodovnikov 2008 from Sabah (Borneo) are presented.